Gyroids: Tuning the Refractive Index in Gyroid Photonic Crystals via Lead‐Chalcogenide Nanocrystal Coating (Advanced Optical Materials 2/2016). Issue 2 (February 2016) - Goi, Elena; Mashford, Benjamin S.; Cumming, Benjamin P.; Gu, Min
Abstract : The chitin gyroid networks inside the butterfly Callophry Rubi wing scales are responsible for the bright green colour of their wings. On page 226, M. Gu and co‐workers replicate these gyroid networks and enhance their optical properties by increasing their refractive index. In this image, a butterfly profile is superimposed over a gyroid photonic crystal coated with PbS nanocubes and green laser beams, suggesting that, with laser fabrication and nanocrystal coatings, biomimetics are now being pushed to another level.